Tortilla Flat Movie Still - MGM:::Creator::::::::::::
Pilon (Spencer Tracy) and Dolores 'Sweets' Ramirez (Hedy Lamarr) in MGM's adaptation of John Steinbeck's novel. RESTRICTED USE Digital copy only. No hard copy.